Development of a Model of the Regional Economic System of the Subject of the Russian Federation - D. M. Zhuravlev (Модернизация, инновация, развитие, 2020)
Purpose: development of an economic-mathematical model for quantifying the economic processes of the constituent entities of the Russian Federation as part of the implementation of regional strategic planning procedures as an instrument for solving the problems of modernizing the Russian economy. To achieve this goal, the following tasks were solved: requirements for the model were formulated; composition fixation and categorization of economic processes completed; the layout of numerical indicators; justified the use of the modeling method; the proof of model performance.Methods: in the study of the problem, the search and development of solutions, methods of comparative analysis, economic and mathematical modeling (regression analysis, correlation analysis, factor analysis, index methods), statistical data processing methods, as well as specially developed application software were used. The regional economic system is considered as a structure that includes a number of autonomous subsystems, each of which is characterized by certain objectively measurable indicators.Results: an economic-mathematical model of the regional economic system of the subject of the Russian Federation has been developed, the functionality of which is sufficient to justify causal relationships between indicators characterizing its current state. Seven systemic economic processes are formalized, the corresponding pairs of «factor-indicator» are arranged, where the factor is an indicator directly controlled by regional authorities, and the indicator mainly shows the macroeconomic quality and dynamics of the process. The proof of the model’s performance was carried out by the experimental method, including in the calculations the indicators of the constituent entities of the Russian Federation that are part of the North-West, Volga and North Caucasus federal districts.Conclusions and Relevance: applying the developed methodological and practical approaches in practice, it is possible to reasonably solve the problems of regional strategic planning, that is, to form a system of priority long-term guidelines that can be achieved using the appropriate set of measures. It is assumed that the applied solution developed for the purposes of this study, subject to its refinement and adjustment to the tasks of a particular region, can become the core of a development management decision support system.